HLA class I-restricted MYD88 L265P-derived peptides as specific targets for lymphoma immunotherapy. (4th March 2017) - Nelde, Annika; Walz, Juliane Sarah; Kowalewski, Daniel Johannes; Schuster, Heiko; Wolz, Olaf-Oliver; Peper, Janet Kerstin; Cardona Gloria, Yamel; Langerak, Anton W.; Muggen, Alice F.; Claus, Rainer; Bonzheim, Irina; Fend, Falko; et al.
ABSTRACT: Genome sequencing has uncovered an array of recurring somatic mutations in different non-Hodgkin lymphoma (NHL) subtypes. If affecting protein-coding regions, such mutations may yield mutation-derived peptides that may be presented by HLA class I proteins and recognized by cytotoxic T cells. A recurring somatic and oncogenic driver mutation of the Toll-like receptor adaptor protein MYD88, Leu265Pro (L265P) was identified in up to 90% of different NHL subtype patients. We therefore screened the potential of MYD88 L265P -derived peptides to elicit cytotoxic T cell responses as tumor-specific neoantigens. Based on in silico predictions, we identified potential MYD88 L265P -containing HLA ligands for several HLA class I restrictions. A set of HLA class I MYD88 L265P -derived ligands elicited specific cytotoxic T cell responses for HLA-B*07 and -B*15. These data highlight the potential of MYD88 L265P mutation-specific peptide-based immunotherapy as a novel personalized treatment approach for patients with MYD88 L265P+ NHLs that may complement pharmacological approaches targeting oncogenic MyD88 L265P signaling.